2002
DOI: 10.1021/np020220l
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of New Sweet Triterpene Saponins from Albizia myriophylla

Abstract: Five new oleanane-type triterpene saponins, albiziasaponins A-E (1-5), were isolated from the stems of Albizia myriophylla collected in Thailand, together with two known triterpene saponins, licorice-saponin F3 and yunganoside B(1). The structures of the new compounds were elucidated on the basis of chemical and physicochemical evidence. In addition, when sensory tests were performed on sweetness, albiziasaponin B (2), with a carbonyl group at the C-30 position, was found to show a potent sweetness intensity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 7 publications
0
49
0
3
Order By: Relevance
“…Our present finding is in accordance with previous clinical study, in which a mouthwash of A. myriophylla was shown to significantly reduce mutans streptococci counts in saliva of schoolchildren (Cholticha et al, 2006). Previous phytochemical studies have revealed the presence of phenolic acids, iminosugars, triterpene saponins, lignan glycosides, and alkaloids (Ito et al, 1994;Yoshikawa et al, 2002;Asano et al, 2005;Panmei et al, 2007). Some of these chemical groups such as phenolics and alkaloids have been established to be the major phytochemical classes of antibacterial metabolites (Samy & Gopalakrishnakone, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Our present finding is in accordance with previous clinical study, in which a mouthwash of A. myriophylla was shown to significantly reduce mutans streptococci counts in saliva of schoolchildren (Cholticha et al, 2006). Previous phytochemical studies have revealed the presence of phenolic acids, iminosugars, triterpene saponins, lignan glycosides, and alkaloids (Ito et al, 1994;Yoshikawa et al, 2002;Asano et al, 2005;Panmei et al, 2007). Some of these chemical groups such as phenolics and alkaloids have been established to be the major phytochemical classes of antibacterial metabolites (Samy & Gopalakrishnakone, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Many members of this genus are important in traditional medicines in some Asian and African countries (Kokwaro, 1976). Albizia myriophylla Benth (Thai local name ''Cha Em Thai'') is widely distributed in southeastern Asian countries (Yoshikawa et al, 2002). It has been reported in the Thai and the Vietnamese systems of traditional medicines that the stems of this plant have been used to substitute for licorice due to their sweetness (Yoshikawa et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Albizia myriophylla Benth (Thai local name ''Cha Em Thai'') is widely distributed in southeastern Asian countries (Yoshikawa et al, 2002). It has been reported in the Thai and the Vietnamese systems of traditional medicines that the stems of this plant have been used to substitute for licorice due to their sweetness (Yoshikawa et al, 2002). Albizia myriophylla is among the most important medicinal plant and is used alone or in combination with other medicinal plants in various Thai herbal formulas, especially those for remedy of oral diseases including dental caries and aphthous ulcer (Neamsuvan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This medicine has also been used as an aromatic stomachic and anti-inflammatory agent. 1,2) In the course of our characterization studies on traditional Thai medicines, [3][4][5][6][7][8][9][10][11][12][13][14][15][16] we previously reported six new sesquiterpenes named (ϩ)-and (Ϫ)-comosols, comosones I, II, and III, and dimethoxycurcumenone from the methanolic extract of the rhizomes of C. comosa together with 26 known sesquiterpenes. 17,18) As a continuing study on this natural medicine, we additionally isolated three new monoterpenes, comosoxide A (1), comosoxide B (2), and comososide (3), together with 7 known compounds.…”
mentioning
confidence: 99%
“…17,18) As a continuing study on this natural medicine, we additionally isolated three new monoterpenes, comosoxide A (1), comosoxide B (2), and comososide (3), together with 7 known compounds. This paper deals with the isolation and structure elucidation of three new constituents (1)(2)(3).…”
mentioning
confidence: 99%